Study on the Influence of Tectonic Stress on Stability of Horseshoe-Shaped Tunnels - Xin Lv; Shuzhi Wang; Yu Qiu; Xiangxin Liu (Advances in Materials Science and Engineering)
While the tunnel is in the high tectonic stress environment and surrounding rock of tunnel has the characteristics of soft texture and stronger expansion, the preference of tunnel shape is horseshoe. An elastic-plastic model is analyzed by complex function theory in accordance with the deformation characteristics of a horseshoe-shaped tunnel in an engineering site. The numerical model of the tunnel is built by FLAC3D, and the influence of the magnitude and direction of structural stress on the horseshoe-shaped tunnel is studied in detail. Finally, the security support of the tunnel is discussed. Results show that the stress concentration phenomenon is easily focused on the left, right, and bottom sides of the tunnel; these places should therefore be the focus of attention of tunnel stability analysis. The magnitude and direction of tectonic stress greatly affect the stability of the horseshoe-shaped tunnel. Similarly, the magnitude of tectonic stress can significantly affect the deformation state of the tunnel. The direction of tectonic stress mainly reflects the orientation of the tunnel. In addition, the orientation of the tunnel should be arranged along the maximum direction of principal stress.